5, 8-Dihydroxy-4 ′, 7-dimethoxyflavone Attenuates TNF-α-Induced Expression of Vascular Cell Adhesion Molecule-1 through EGFR/PKCα/PI3K/Akt/Sp1-Dependent Induction of Heme Oxygenase-1 in Human Cardiac Fibroblasts. (4th March 2022) - Yang, Chien-Chung; Hsiao, Li-Der; Shih, Ya-Fang; Lin, Hsin-Hui; Yang, Chuen-Mao
Abstract : Recently, we found that 5, 8-dihydroxy-4 ', 7-dimethoxyflavone (DDF) upregulated the expression of heme oxygenase (HO)-1 via p38 mitogen-activated protein kinase/nuclear factor-erythroid factor 2-related factor 2 (MAPK/Nrf2) pathway in human cardiac fibroblasts (HCFs). However, the alternative processes by which DDF induces the upregulation of HO-1 expression are unknown. Activation of epidermal growth factor receptor (EGFR), phosphoinositide 3-kinase/protein kinase B (PI3K/Akt), and protein kinase C (PKC) α may initiate specificity protein (Sp)1 activity, which has been reported to induce expression of antioxidant molecules. Thus, we explored whether these components are engaged in DDF-induced HO-1 upregulation in HCFs. Western blotting, promoter-reporter analyses, and real-time polymerase chain reactions were adopted to measure HO-1 and vascular cell adhesion molecule (VCAM)-1 expressions in HCFs. Respective small interfering (si)RNAs and pharmacological inhibitors were employed to investigate the signaling components engaged in DDF-induced HO-1 upregulation. The chromatin immunoprecipitation assay was conducted to detect the binding interaction of Sp1 and antioxidant response elements (ARE) on the promoter of HO-1. An adhesion assay of THP-1 monocyte was undertaken to examine the functional effect of HO-1 on tumor necrosis factor (TNF)- α -induced VCAM-1 expression. DDF stimulated the EGFR/PKC α /PI3K/Akt pathway leading to activation of Sp1 in HCFs. The roles of these protein kinases in HO-1 induction were ensured by transfection with their respective siRNAs. Chromatin immunoprecipitation assays revealed the interaction between Sp1 and the binding site of proximal ARE on the HO-1 promoter, which was abolished by glutathione, AG1478, Gö6976, LY294002, or mithramycin A. HO-1 expression enhanced by DDF abolished the monocyte adherence to HCFs and VCAM-1 expression induced by TNF- α . Pretreatment with an inhibitor of HO-1: zinc protoporphyrin IX reversed these inhibitory effects of HO-1. We concluded that DDF-induced HO-1 expression was mediated via an EGFR/PKC α /PI3K/Akt-dependent Sp1 pathway and attenuated the responses of inflammation in HCFs.